A glass with low viscosity at high temperature, high strain point temperature, and a preparation method and application thereof

CN122977698APending Publication Date: 2026-10-27HENAN XINGYANG PHOTOELECTRIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611213987.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0010]为解决现有无碱玻璃高应变点温度与低高温粘度难以兼顾的技术难题,本发明提供一种高温粘度低、应变点温度高的玻璃及其制备方法和应用,有效克服了现有同类玻璃在生产过程中高温粘度大的技术难题,缓解了该类玻璃熔融温度过高、生产能耗大、窑炉侵蚀严重的生产痛点,同时充分满足了LTPS制程对基板玻璃高应变点温度的严苛要求

Benefits of technology

本发明通过组分种类以及HVI值、VTVI值、n1值、n2值的协同配合,共同调控各组分的含量,实现了高温粘度低和应变温度高的效果,控制T100温度≤1741℃,应变点温度(Tst值)≥720℃,如将T100温度降低到了1708℃,应变点温度(Tst值)达到了756℃;如T100为1741℃,同时应变点温度(Tst值)达到了754℃。若是HVI值、VTVI值、n1值、n2值不在设定范围之内,则制备的玻璃,容易出现T100温度过高,产品难以生产;或者虽T100温度不高,但应变点温度Tst同样较低,无法满足LTPS制程对于基板玻璃应变点温度要求等问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a kind of glass with low high-temperature viscosity and high strain point temperature, its preparation method and application, belong to glass technical field, the glass described in the application includes the following components by mole percentage: 63-73% of SiO2, 9-16% of Al2O3, 0-6% of B2O3, 3-7% of MgO, 3-9% of CaO, 0.1-3% of SrO, 0.2-7% of BaO, 0-3% of ZnO, 0.05-0.4% of SnO2 and Y2O3 and La2O3, the sum of Y2O3 and La2O3 is 0-2%.The application effectively overcomes the technical difficulties of the same kind of glass with large high-temperature viscosity in the production process, alleviates the production pain points of the glass with high melting temperature, large production energy consumption and serious kiln erosion, and fully meets the stringent requirements of LTPS process on high strain point temperature of substrate glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass technology, specifically to a glass with low high-temperature viscosity and high strain point temperature, its preparation method, and its application, applicable to the field of high-end optoelectronic glass and display panel manufacturing materials. Background Technology

[0002] Organic light-emitting diodes (OLEDs) are a self-emissive display technology with numerous outstanding technical advantages, such as high contrast, wide color gamut, and fast response speed. They are currently the mainstream technology for high-end smartphones, wearable displays, and foldable devices. Rigid OLED devices rely on driving elements fabricated on a glass substrate to achieve pixel switching and driving control. In the mainstream manufacturing processes for driving elements, the traditional α-Si process has low mobility and high leakage current, which cannot meet the high-precision and high-refresh-rate driving requirements of OLEDs. The new low-temperature polycrystalline silicon (LTPS) process, however, has a carrier mobility that is more than 100 times higher than α-Si, which can significantly reduce the size of driving elements, increase pixel aperture ratio, support ultra-high PPI and high refresh rate displays, and integrate peripheral driving circuits, perfectly adapting to the high-end process requirements of both rigid and flexible OLEDs.

[0003] The production process of low-temperature polycrystalline silicon thin-film transistors (LTPS-TFTs) is more complex, requiring the deposition of multiple organic light-emitting layers and metal electrodes through high-temperature evaporation and annealing processes after the preparation of the driving element layer. The overall process peak temperature can reach 550-600℃, with more high-temperature cycles and more stringent thermal loads. As the carrier substrate for the entire rigid LTPS-TFT process, the thermal stability of the substrate glass directly determines the panel yield and display quality, with the strain point temperature being a core critical indicator.

[0004] Generally speaking, T 100 The lower the temperature, the lower the temperature required for the molten glass to reach that viscosity. This makes the glass easier to melt, which is beneficial for improving the clarification effect of the molten glass, extending the furnace life, and reducing energy consumption. Currently, the mainstream strain point temperature requirement for substrate glass in LTPS-TFT processes has reached 720℃, and some high-end products even require strain point temperatures greater than 740℃. However, as the strain point temperature increases, the high-temperature viscosity of the glass generally also increases accordingly. The viscosity of this type of glass is T. 100 The melting and clarifying temperature is generally ≥1710℃. The higher melting and clarifying temperature not only consumes more energy, but also aggravates the erosion of the kiln structure and forming materials.

[0005] In existing technologies, the development of substrate glasses mainly focuses on improving the high strain point, while research on reducing high-temperature viscosity is relatively limited. Chinese patent application CN108341595A discloses a glass composition, a glass with low inclusion content, its preparation method, and its applications. The raw materials for glass preparation are uniformly mixed with NH4NO3 and then melt-treated. The resulting glass has a strain point temperature ≥710℃, but its high-temperature viscosity is the temperature T corresponding to 100 poise. 100 With temperatures ≥1730℃, and up to 1795℃, melting and clarifying glass is extremely difficult and requires enormous energy.

[0006] Chinese patent application CN101400614A discloses a glass with good dimensional stability with temperature change. The thermal stability of the glass is adjusted by adjusting the molar ratio of alkaline earth metal oxide to alumina. The strain point temperature of the glass is ≥700℃, and the temperature corresponding to a viscosity of 200 poise is about 1665℃. The T100 temperature is not specified.

[0007] Chinese patent application CN101544466A discloses a substrate glass raw material and its preparation method. The refining temperature of the substrate glass is 1650℃, but the refining viscosity is not specified, nor is the T value described. 100 Temperature, and the use of highly toxic and carcinogenic arsenic oxide and antimony oxide as clarifying agents, have been prohibited by current environmental regulations;

[0008] Chinese patent application CN117923792A discloses a low wetting angle glass substrate and its preparation method. By controlling the content of each component and introducing a small amount of K₂O, the wetting angle is reduced. The strain point temperature of this glass can reach 712℃-750℃, but the document does not describe its strain point temperature (T). 100 Temperature, and the introduction of K2O can lead to the precipitation of alkali ions at high temperatures, reducing the yield and reliability of thin-film transistor (TFT) devices.

[0009] In summary, current industry research on LTPS high-temperature substrate glass mainly focuses on improving strain point temperature, controlling expansion rate, and increasing modulus, with less research on reducing high-temperature viscosity. Therefore, developing a substrate glass that can meet other technical requirements and achieve low high-temperature viscosity and high strain point temperature is of great practical significance for the manufacturing and widespread use of LTPS high-temperature substrate glass. Summary of the Invention

[0010] To address the technical challenge of balancing high strain point temperature and low high-temperature viscosity in existing alkali-free glass, this invention provides a glass with low high-temperature viscosity and high strain point temperature, along with its preparation method and applications. This effectively overcomes the technical difficulty of high high-temperature viscosity in the production process of similar existing glasses, alleviating the production pain points of excessively high melting temperature, high energy consumption, and severe furnace erosion in such glasses. At the same time, it fully meets the stringent requirements of the LTPS process for high strain point temperature of the substrate glass.

[0011] To achieve the above objectives, the present invention provides a glass with low high-temperature viscosity and high strain point temperature, comprising the following components by molar percentage: 63%-73% SiO2, 9%-16% Al2O3, 0%-6% B2O3, 3%-7% MgO, 3%-9% CaO, 0.1%-3% SrO, 0.2%-7% BaO, 0%-3% ZnO, 0.05%-0.4% SnO2, and Y2O3 and La2O3, wherein the sum of Y2O3 and La2O3 is 0%-2%.

[0012] The functions and content limits of each component in the formula are based on the following: SiO2: A fundamental network component of silicate glass, ensuring its high chemical stability and mechanical strength. When the content is below 63%, the network structure integrity is low, the coefficient of thermal expansion increases, and stress is generated due to thermal mismatch with silicon materials during TFT-LCD processes. When the content is above 73%, the glass melt viscosity increases significantly, making melting and clarification difficult. Therefore, the preferred range is 63%-73%.

[0013] Al2O3: A network intermediate. When there is sufficient free oxygen in the glass, it can form aluminum-oxygen tetrahedra [AlO4], effectively improving the strength of the silicate glass network structure, thereby further improving the glass's elastic modulus, reducing the coefficient of thermal expansion, and enhancing chemical stability. A content below 9% is not conducive to increasing the glass's strain point temperature, while a content above 16% significantly increases high-temperature viscosity and also raises the liquidus temperature, increasing the risk of crystallization. Therefore, the preferred range is 9%-16%.

[0014] B2O3: The core element for adjusting the high-temperature viscosity and strain point temperature of glass. In alkali-free aluminosilicate glass systems, it can effectively reduce the viscosity of glass at high temperatures and participate in the formation of glass network at low temperatures, thereby increasing the strain point temperature of glass. However, when the content is too high, it will exceed the boron anomalous point and increase the high-temperature viscosity of glass. On the other hand, it will be detrimental to the acid corrosion resistance of glass. Therefore, the preferred range is 0%-6%.

[0015] MgO helps improve the chemical stability and mechanical properties of glass. When partially replacing CaO, it can adjust the viscosity-temperature curve, resulting in a longer viscosity profile, which is not conducive to rapid molding. On the other hand, the viscosity-reducing effect of this element at high temperatures is not as good as that of CaO, which is not conducive to manufacturing glass with low high-temperature viscosity and high strain point temperature. Therefore, the preferred range is 3%-7%.

[0016] CaO: In alkali-free glass systems, it can significantly reduce high-temperature viscosity and increase strain point temperature. It is also an important element for regulating glass properties. When the content is too high, it will increase the coefficient of thermal expansion on the one hand and improve the glass crystallization ability on the other hand. Therefore, the preferred range is 3%-9%.

[0017] SrO: It can be used in conjunction with CaO and MgO to form a mixed alkaline earth metal effect to increase the strain point temperature. This element can reduce the high-temperature viscosity of glass, but it will also increase CTE and density, and reduce modulus and strain point temperature. The amount used should not be too high, so the preferred range is 0.1%-3%.

[0018] BaO: It can effectively reduce the high-temperature viscosity of glass, which is beneficial for glass melting and clarification, thereby further saving energy. However, this element will also lower the strain point temperature and increase the glass density. Therefore, the amount used should not be too high, and the preferred range is 0.2%-7%.

[0019] ZnO: It can improve melt uniformity and surface quality, and can be used as an amphoteric oxide to adjust the network structure, which is beneficial to shorten the glass content. The preferred range is 0%-3%.

[0020] SnO2: A highly efficient clarifying agent that releases oxygen at high temperatures, helping to eliminate bubbles. The preferred content is 0.05%-0.4%, which balances clarification effect and avoids secondary bubbles.

[0021] Y2O3 and La2O3 are rare earth oxides that have similar functions in aluminoborosilicate glass. They enhance the density of the glass network structure through the accumulation effect of high field strength ions, thereby further improving the glass's elastic modulus, strain point, resistivity, and other properties. However, they are expensive and can easily increase the glass density. The preferred combined amount of the two is 0-2%.

[0022] As mentioned above, glass preparation requires a variety of components. To better control the content of each component and the relationship between their dosages, thereby obtaining glass with low high-temperature viscosity and high strain point temperature, this invention designs parameters such as the high-temperature viscosity index (HVI) and the temperature-viscosity change index (VTVI).

[0023] Furthermore, the high-temperature viscosity index (HVI) of the glass with low high-temperature viscosity and high strain point temperature is 1675-1745. The formula for calculating the high-temperature viscosity index (HVI) is as follows: HVI=6.54×[Al2O3]+4.89×[SiO2]-4.91×[B2O3]-2.53×[MgO]-4.24×[CaO]-4.62× [SrO]-6.32×[BaO]-3.12×[ZnO]-4.64×[Y2O3]-4.58[La2O3]-2.27[SnO2]+1372; In the formula, [component] represents the molar percentage content of the corresponding component multiplied by 100. For example, if the molar percentage content of SiO2 is 70%, then [component] = 70% × 100 = 70.

[0024] Furthermore, the temperature viscosity change index (VTVI) of the glass with low high-temperature viscosity and high strain point temperature is 930-1010. The formula for calculating the temperature viscosity index (VTVI) is as follows: VTVI=19.5×[Al2O3]+22.2×√[SiO2]-13.8×[B2O3]-1.5×[MgO]-11.3×[CaO]-3. 4×[SrO]-3.8×[BaO]-9.7×[ZnO]-3.1×[Y2O3]-2.8×[La2O3]-1.2×[SnO2]+664; In the formula, [component] represents the molar percentage content of the corresponding component × 100. √ represents the square root.

[0025] The High-Temperature Viscosity Index (HVI) and the Viscosity-Temperature Variation Index (VTVI) are two core parameters of this invention used to precisely coordinate the high-temperature viscosity and strain point temperature of glass. They are defined as follows: HVI is used to directly quantify and evaluate the Celsius temperature T corresponding to a viscosity of 100 poise. 100 VTVI is used to evaluate glass T 100 Temperature difference between the temperature and the strain point temperature of the glass. By adjusting the content of the network forger, the network exogenous body, and temperature-sensitive elements, the relationship between high-temperature viscosity and strain point temperature can be coordinated, and the overall temperature-viscosity properties of the glass can be precisely controlled, making it easier to obtain glass with low high-temperature viscosity and high strain point temperature.

[0026] The preferred HVI value range of this invention is 1675-1745, controlling T 100 If the temperature is not too high, the HVI value will be too high, resulting in excessively high viscosity of the material at high temperatures, which will increase the difficulty of glass melting and clarification, and raise the process difficulty and glass cost. If the temperature is too low, it will be impossible to achieve a high strain point.

[0027] The optimal range for the VTVI value is 930-1010, balancing the requirements for both low and high temperature viscosity and high strain point temperature. If the value is too high, it will be difficult to meet both requirements; if it is too low, the viscosity will change too quickly with temperature, increasing the difficulty of glass edge forming. By coordinating the relationship between these two indicators and actual production applications, the requirements for both low and high temperature viscosity and high strain point temperature of the glass can be achieved.

[0028] Furthermore, the glass shown, which has low high-temperature viscosity and high strain point temperature, comprises the following components by molar percentage: 63%-72% SiO2, 10%-16% Al2O3, 0%-6% B2O3, 3%-7% MgO, 3%-9% CaO, 0.1%-3% SrO, 1%-7% BaO, 0%-2.5% ZnO, 0.05%-0.4% SnO2, and Y2O3 and La2O3, with the sum of Y2O3 and La2O3 being 0%-2%.

[0029] Furthermore, the high-temperature low viscosity and high strain point temperature glass comprises, by molar percentage, the following components: 63%-72% SiO2, 10%-15.8% Al2O3, 0%-5.5% B2O3, 3.5%-7% MgO, 3.5%-9% CaO, 0.1%-2.5% SrO, 1%-6.5% BaO, 0.1%-2.5% ZnO, 0.05%-0.4% SnO2, and Y2O3 and La2O3, the total of Y2O3 and La2O3 being 0%-2%.

[0030] Furthermore, n1 = (B2O3 + CaO + ZnO) / (B2O3 + CaO + ZnO + MgO + SrO + SnO2 + Y2O3 + La2O3 + BaO) = 0.25 - 0.7, where each component in the formula is its molar percentage.

[0031] By using n1, the proportion of the coordinating element in the total viscosity-reducing elements is ensured, which is more conducive to coordinating the relationship between high-temperature viscosity and strain point temperature.

[0032] Furthermore, n2 = (B2O3 + CaO + ZnO + MgO + SrO + SnO2 + Y2O3 + La2O3 + BaO) / (SiO2 + Al2O3) = 0.15 - 0.40, where each component in the formula is its molar percentage.

[0033] By controlling the ratio of viscosity-reducing elements to viscosity-increasing elements using n2, the high-temperature viscosity can be adjusted to prevent it from becoming too high.

[0034] Furthermore, the high-temperature viscosity index (HVI) is 1675-1743, optimized HVI is 1675-1732; optimized HVI is 1675-1725; optimized HVI is 1684-1718; optimized HVI is 1684-1708.

[0035] Furthermore, the temperature viscosity variation index (VTVI) is 946-991; optimally, the VTVI is 946-976.

[0036] Furthermore, the glass shown, which has low high-temperature viscosity and high strain point temperature, comprises the following components by molar percentage: 63%-72% SiO2, 10%-16% Al2O3, 0%-6% B2O3, 3%-7% MgO, 3%-9% CaO, 0.1%-3% SrO, 1%-7% BaO, 0%-2.5% ZnO, 0.05%-0.4% SnO2, and Y2O3 and La2O3, with the sum of Y2O3 and La2O3 being 0%-2%.

[0037] The high-temperature viscosity index (HVI) is 1684-1743; the temperature viscosity change index (VTVI) is 946-991; n1 = 0.29-0.65; n2 = 0.23-0.29.

[0038] Setting this parameter range is beneficial for controlling T. 100 With a temperature ≤1720℃ and a strain point temperature (Tst value) ≥720℃, this design avoids the production problem of compressed glass forming temperature range and increased glass forming difficulty.

[0039] Furthermore, the glass shown, characterized by low high-temperature viscosity and high strain point temperature, comprises, by molar percentage, the following components: 64.25%-70% SiO2, 11%-15.5% Al2O3, 0.8%-5% B2O3, 3%-4.8% MgO, 3%-7.5% CaO, 0.3%-3% SrO, 1.3%-7% BaO, 0.2%-2% ZnO, 0.1%-0.15% SnO2, 0%-0.7% Y2O3, and 0%-0.3% La2O3; The high-temperature viscosity index (HVI) is 1684-1708; the temperature viscosity change index (VTVI) is 946-976; n1 = 0.29-0.62; n2 = 0.23-0.28.

[0040] Setting this parameter range is beneficial for controlling T. 100 With a temperature ≤1710℃ and a strain point temperature (Tst value) ≥730℃, it avoids the production problem of the glass forming temperature range being compressed, which increases the difficulty of glass forming.

[0041] Furthermore, the glass shown, characterized by low high-temperature viscosity and high strain point temperature, comprises, by molar percentage, the following components: 64.25%-70% SiO2, 11%-14% Al2O3, 1%-4% B2O3, 3%-4.2% MgO, 3%-6.7% CaO, 0.3%-3% SrO, 3%-7% BaO, 1%-2% ZnO, 0.1%-0.15% SnO2, 0.05%-0.7% Y2O3, and 0.2%-0.3% La2O3; The high-temperature viscosity index (HVI) is 1684-1698; the temperature viscosity change index (VTVI) is 946-960; n1 = 0.29-0.57; n2 = 0.23-0.28.

[0042] Setting this parameter range is beneficial for controlling T. 100 With a temperature ≤1700℃ and a strain point temperature (Tst value) ≥730℃, it avoids the production problem of the glass forming temperature range being compressed, which increases the difficulty of glass forming.

[0043] The method for preparing the glass with low viscosity at high temperatures and high strain point temperature includes the following steps: (1) Mix all components according to their molar percentages to obtain the batch material; (2) Feed the material at 550-650℃, heat the batch material to 1450-1550℃ at a rate of 8-12℃ / min, and hold for 1.5-2.5h; then heat to 1600-1700℃ at a rate of 2-4℃ / min, and hold for 18-22h. Stir and clarify during the holding period to obtain a homogeneous and clear glass melt. (3) Pour the glass melt, harden it and then anneal it at 750-850℃ for 1.5-2.5h, and then cool it down to room temperature at a rate of 0.1-0.3℃ / min.

[0044] Furthermore, in step (1), each component is selected from electronic-grade raw materials with a purity of ≥99.5%, and the total content of alkali metal oxide impurities is controlled to be <0.05wt%.

[0045] Furthermore, in step (2), the stirring rate for clarification is 30 rpm.

[0046] Further, in step (1), the weight percentage of each component is calculated according to the molar percentage of each component, and the batching list is calculated based on the weight percentage. The batching is then used to obtain the compound and mixed evenly.

[0047] The above-described technical solution of the present invention has at least the following beneficial effects: This invention achieves low high-temperature viscosity and high strain temperature by synergistically controlling the content of each component through the types of components and the HVI, VTVI, n1, and n2 values, thereby controlling T 100 Temperature ≤1741℃, strain point temperature (Tst value) ≥720℃, if T 100 The temperature dropped to 1708℃, and the strain point temperature (Tst value) reached 756℃; (e.g., T...) 100 The temperature reached 1741℃, and the strain point temperature (Tst value) reached 754℃. If the HVI, VTVI, n1, and n2 values ​​are not within the set range, the prepared glass is prone to T... 100 If the temperature is too high, the product will be difficult to manufacture; or although T 100 The temperature is not high, but the strain point temperature Tst is also low, which cannot meet the requirements of the LTPS process for the strain point temperature of the substrate glass.

[0048] This invention utilizes the HVI formula to limit the HVI range to 1675-1745 by adjusting the content of elements such as B2O3, CaO, and MgO in the raw material. This effectively alleviates the problems of excessive energy consumption and severe damage to the kiln structure caused by excessively high temperatures during glass production. It not only effectively reduces the difficulty of the process but also helps to improve the glass production yield and further reduce glass production costs, thus greatly promoting the improvement of the overall competitiveness of the product.

[0049] This invention utilizes the VTVI formula to limit the VTVI value range to 930-1010 by adjusting the content of elements such as B2O3, CaO, and ZnO in the feed formula. This range coordinates the relationship between high-temperature viscosity and strain point temperature, which helps to achieve low high-temperature viscosity while ensuring a high strain point temperature. It can fully meet the requirements of the LTPS process for high strain point of the substrate glass, thus improving the process yield.

[0050] Based on the above-mentioned HVI and VTVI formulas for regulating the feed formulation, further limiting the dosage relationship between different components through n1 and n2 is beneficial for reducing T. 100 Simultaneously with temperature control, a high strain point temperature (Tst value) is obtained. That is, this invention solves the Tst problem through the synergistic combination of component types and HVI, VTVI, n1, and n2 values. 100 This addresses the technical challenge of excessively high temperatures and excessively low strain point temperatures (Tst values) in products, while also avoiding the production problem of compressed glass forming temperature range and increased glass forming difficulty.

[0051] Furthermore, this invention establishes a rapid verification mechanism for raw material ratios by setting quantitative formulas for HVI, VTVI, n1, and n2 values. Subsequent experimental verification is only conducted when the raw material ratios meet a preset threshold range, significantly shortening the R&D cycle, reducing material costs, and greatly improving the efficiency of glass formulation optimization. Detailed Implementation

[0052] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.

[0053] Examples 1-8 A method for preparing glass with low viscosity at high temperatures and high strain point temperature includes the following steps: (1) Each component shall be made of electronic grade raw materials with a purity of ≥99.5%, and the total content of alkali metal oxide impurities shall be controlled to <0.05wt%; the actual amount of each raw material shall be calculated and the sample shall be weighed accurately according to the molar percentage of each component in Table 1. (2) Place the weighed raw materials in a mixing machine and mix for ≥3 hours to ensure that the batch is fully mixed and obtain the batch; (3) Place 1.4 kg of well mixed batch material into a 1.8 L platinum crucible, place it in a high temperature melting furnace at 600 °C, heat it to 1500 °C at a rate of 10 °C / min, hold it for 2 h, and then further heat it to 1680 °C at a rate of 3 °C / min and hold it for 20 h for clarification. During the holding period, continuously stir the glass melt in the crucible at a speed of 30 rpm to assist in the clarification and obtain the glass melt. (4) Take out the clarified glass liquid from the furnace, pour it into a steel mold, and after the surface hardens, immediately transfer it to an 800℃ furnace for annealing for 2 hours, and then cool it down to room temperature at a rate of 0.2℃ / min.

[0054] Table 1. Glass composition (molar %) of Examples 1-8

[0055] The glass samples from Examples 1-8 were subjected to performance tests, and the test methods are as follows: Viscosity at 100 poise temperature (T) 100 (Referring to ASTM C-965 standard, the high-temperature viscosity-temperature profile of glass was determined using the rotating molten glass method, with particular attention paid to T.) 100 The indicator is in °C. Strain point temperature (T) st): The strain point temperature of glass was measured using the glass fiber counterweight elongation method according to ASTM C-336 standard, and the unit is °C; Young's modulus (E): The Young's modulus of glass is determined by the resonance method according to ASTM C-623 standard, and the unit is GPa; Glass density (ρ): The density of glass was determined using a density balance method according to ASTM C-693 standard, and the unit is g / cm³. 3 ; Coefficient of thermal expansion (CTE): The coefficient of thermal expansion of glass is determined using a horizontal dilatometer according to ASTM E-228 standard. The test temperature range is 50-350℃, and the unit is 10. -7 / ℃; Liquidus temperature: The liquidus temperature of glass was determined using the gradient furnace method according to Method A in ASTM C-829-2015, with a holding time of 24 hours. The unit is °C.

[0056] The test results are shown in Table 2: Table 2 Glass properties of Examples 1-8

[0057] As can be seen from the components of Examples 1-8 and the corresponding glass property data in Table 2, this invention utilizes the HVI and VTVI formulas to coordinate the relationship between high-temperature viscosity and strain point temperature by adjusting the content of corresponding elements, thus producing glass with low high-temperature viscosity and high strain point temperature. The overall fit of the formulas is very good. Among them, Example 2 is the optimal embodiment of this invention, not only T 100 The temperature was lowered to 1708℃, achieving a high strain point temperature of 756℃. Furthermore, this embodiment achieved a Young's modulus of 85.5 GPa and a CTE value of 36.98 × 10⁻⁶. -7 / ℃, glass density is 2.57g / cm³ 3 The above indicators are all applicable to LTPS high-temperature substrate glass applications and can fully meet the technical requirements for substrate glass in OLED display technology manufacturing processes.

[0058] Examples 9-12 and Comparative Examples 1-4 A method for preparing glass with low viscosity at high temperatures and high strain point temperature includes the following steps: (1) Electronic grade raw materials with a purity of ≥99.5% are selected for each component, and the total content of alkali metal oxide impurities is controlled to <0.05wt%; calculate the actual amount of each raw material according to the molar percentage of each component in Table 3 and weigh the sample accurately; (2) Place each raw material in a mixing machine and mix for ≥3 hours to ensure that the batch is fully mixed and obtain the batch material; (3) Place 1.4 kg of well mixed batch material into a 1.8 L platinum crucible, place it in a high temperature melting furnace at 600 °C, heat it to 1500 °C at a rate of 10 °C / min, hold it for 2 h, and then further heat it to 1680 °C at a rate of 3 °C / min and hold it for 20 h for clarification. During the holding period, continuously stir the glass melt in the crucible at a speed of 30 rpm to assist in the clarification and obtain the glass melt. (4) Take out the clarified glass liquid from the furnace, pour it into a steel mold, and after the surface hardens, immediately transfer it to an 800℃ furnace for annealing for 2 hours, and then cool it down to room temperature at a rate of 0.2℃ / min.

[0059] Table 3 Glass composition (mol%) of Examples 9-12 and Comparative Examples 1-4

[0060] The glass samples of Examples 9-12 and Comparative Examples 1-4 were subjected to performance tests, and the test methods are as follows: Viscosity at 100 poise temperature (T) 100 (Referring to ASTM C-965 standard, the high-temperature viscosity-temperature profile of glass was determined using the rotating molten glass method, with particular attention paid to T.) 100 The indicator is in °C. Strain point temperature (T) st ): The strain point temperature of glass was measured using the glass fiber counterweight elongation method according to ASTM C-336 standard, and the unit is °C; Young's modulus (E): The Young's modulus of glass is determined by the resonance method according to ASTM C-623 standard, and the unit is GPa; Glass density (ρ): The density of glass was determined using a density balance method according to ASTM C-693 standard, and the unit is g / cm³. 3 ; Coefficient of thermal expansion (CTE): The coefficient of thermal expansion of glass is determined using a horizontal dilatometer according to ASTM E-228 standard. The test temperature range is 50-350℃, and the unit is 10. -7 / ℃; Liquidus temperature: The liquidus temperature of glass was determined using the gradient furnace method according to Method A in ASTM C-829-2015, with a holding time of 24 hours. The unit is °C.

[0061] The test results are shown in Table 4: Table 4. Glass properties of Examples 9-12 and Comparative Examples 1-4

[0062] Combining Tables 3 and 4, as shown in Comparative Example 1, when the Al2O3 content is greater than 16%, and the SiO2 value is also high, n2 is relatively small, and HVI and VTVI values ​​are relatively large, resulting in T... 100 The temperature was extremely high, reaching 1802 ℃, resulting in excessively high viscosity and making the product difficult to manufacture.

[0063] Comparative Example 2 shows that the SiO2 content is low, below 63%, while n2 is relatively high and HVI value is relatively low. Although T 100 The temperature is not high, but the strain point temperature Tst is also low, making it impossible to balance the relationship between the two temperatures. In addition, the BaO and SrO values ​​are high in this case, resulting in excessive glass density, which is not conducive to the lightweighting of the glass.

[0064] As shown in Comparative Example 3, although each component meets the set component range requirements, n1 is too small and VTVI value is too high. 100 Under certain conditions, it is impossible to achieve a high strain point temperature (Tst).

[0065] In Comparative Example 4, both VTVI and HVI values ​​were low, T 100 The temperature was 1658℃, while the strain point temperature Tst was as high as 808℃. The excessively high strain point temperature Tst caused T... 100 If the temperature range between the temperature and the strain point temperature Tst is too small, the glass forming temperature range will be compressed, increasing the difficulty of glass forming and which is detrimental to production.

[0066] Example 13 This embodiment is basically the same as embodiment 1, except that: A method for preparing glass with low viscosity at high temperatures and high strain point temperature, characterized by comprising the following steps: (1) Calculate the weight percentage of each component according to the molar percentage of each component, and further calculate the batching list according to the weight percentage, and obtain the batching material and mix it evenly. (2) Feed the batch at 550℃, heat the batch to 1550℃ at a rate of 12℃ / min, and keep it at 1.5h; then heat it to 1700℃ at a rate of 4℃ / min and keep it at 18h. Stir and clarify during the holding period to obtain glass melt. (3) Pour the glass liquid, harden it and anneal it at 850℃ for 1.5h, then cool it down to room temperature at a rate of 0.1℃ / min.

[0067] Example 14 This embodiment is basically the same as embodiment 1, except that: (1) Calculate the weight percentage of each component according to the molar percentage of each component, and further calculate the batching list according to the weight percentage, and obtain the batching material and mix it evenly. (2) Feed the batch at 650℃, heat the batch to 1450℃ at a rate of 8℃ / min, and keep it at that temperature for 2.5h; then heat it to 1600℃ at a rate of 2℃ / min and keep it at that temperature for 22h. Stir and clarify during the holding period to obtain glass melt. (3) Pour the glass liquid, harden it and anneal it at 750℃ for 2.5h, then cool it down to room temperature at a rate of 0.3℃ / min.

Claims

1. A glass with low high-temperature viscosity and high strain point temperature, characterized in that: The product comprises the following components by molar percentage: 63%-73% SiO2, 9%-16% Al2O3, 0%-6% B2O3, 3%-7% MgO, 3%-9% CaO, 0.1%-3% SrO, 0.2%-7% BaO, 0%-3% ZnO, 0.05%-0.4% SnO2, and Y2O3 and La2O3, with the sum of Y2O3 and La2O3 being 0%-2%.

2. The glass with low high-temperature viscosity and high strain point temperature according to claim 1, characterized in that: The product comprises the following components by molar percentage: 63%-72% SiO2, 10%-16% Al2O3, 0%-6% B2O3, 3%-7% MgO, 3%-9% CaO, 0.1%-3% SrO, 1%-7% BaO, 0%-2.5% ZnO, 0.05%-0.4% SnO2, and Y2O3 and La2O3, with the sum of Y2O3 and La2O3 being 0%-2%.

3. The glass with low high-temperature viscosity and high strain point temperature according to claim 1 or 2, characterized in that: The high-temperature viscosity index (HVI) of the glass is 1675-1745. The formula for calculating the high-temperature viscosity index (HVI) is as follows: HVI=6.54×[Al2O3]+4.89×[SiO2]-4.91×[B2O3]-2.53×[MgO]-4.24×[CaO]-4.62× [SrO]-6.32×[BaO]-3.12×[ZnO]-4.64×[Y2O3]-4.58[La2O3]-2.27[SnO2]+1372; In the formula, [component] represents the molar percentage content of the corresponding component × 100.

4. The glass with low high-temperature viscosity and high strain point temperature according to claim 1 or 2, characterized in that: The temperature viscosity change index (VTVI) of the glass is 930-1010; The formula for calculating the temperature viscosity index (VTVI) is as follows: VTVI=19.5×[Al2O3]+22.2×√[SiO2]-13.8×[B2O3]-1.5×[MgO]-11.3×[CaO]-3. 4×[SrO]-3.8×[BaO]-9.7×[ZnO]-3.1×[Y2O3]-2.8×[La2O3]-1.2×[SnO2]+664; In the formula, [component] represents the molar percentage content of the corresponding component × 100.

5. The glass with low high-temperature viscosity and high strain point temperature according to claim 1 or 2, characterized in that: n1 = (B2O3+CaO+ZnO) / (B2O3+CaO+ZnO+MgO+SrO+SnO2+Y2O3+La2O3+BaO) = 0.25-0.7, where each component is its molar percentage.

6. The glass with low high-temperature viscosity and high strain point temperature according to claim 1 or 2, characterized in that: n2=(B2O3+CaO+ZnO+MgO+SrO+SnO2+Y2O3+La2O3+BaO) / (SiO2+Al2O3)=0.15-0.40, where each component is its molar percentage.

7. The glass with low high-temperature viscosity and high strain point temperature according to claim 3, characterized in that: The high-temperature viscosity index (HVI) is 1675-1725.

8. A method for preparing glass with low high-temperature viscosity and high strain point temperature as described in any one of claims 1-7, characterized in that, Includes the following steps: (1) Mix all components according to their molar percentages to obtain the batch material; (2) Feed the material at 550-650℃, heat the batch material to 1450-1550℃ at a rate of 8-12℃ / min, and hold for 1.5-2.5h; then heat to 1600-1700℃ at a rate of 2-4℃ / min, and hold for 18-22h. Stir and clarify during the holding period to obtain a homogeneous and clear glass melt. (3) Pour the glass melt, harden it and then anneal it at 750-850℃ for 1.5-2.5h, and then cool it down to room temperature at a rate of 0.1-0.3℃ / min.

9. The preparation method according to claim 8, characterized in that, In step (1), each component is selected from electronic-grade raw materials with a purity of ≥99.5%, and the total content of alkali metal oxide impurities is controlled to be <0.05wt%.

10. The application of the high-temperature low viscosity and high strain point temperature glass as described in any one of claims 1-7 in optoelectronic glass or display panels.

Citation Information

Patent Citations

  • Glass compositions having high thermal and chemical stability and methods of making thereof

    CN101400614A

  • Crystal liquid substrate glass material and preparation method thereof

    CN101544466A

  • Glass composition, glass low in impurity content and preparation method and application of glass

    CN108341595A

  • Low-wetting-angle glass substrate, preparation method and display panel

    CN117923792A